PROBLEM BASED LEARNING (PBL) PADA MATERI TEOREMA PYTHAGORAS: SUATU ACTION RESEARCH - Tia Safitri; Wahyu Hidayat; Indah Puspita Sari (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
The purpose of this research was to improve student learning outcomes on the Pythagorean theorem material through the use of Problem Based Learning models. The type of research is Classroom Action Research which was conducted during the second cycle. This research was carried out in 5 steps: (1) student orientation to problems (2) organizing students for learning, (3) assisting individual and group investigations, (4) developing and presenting work, (5) analyzing and evaluating the problem solving process. The research subjects were 15 students of class VIII in one of the junior high schools in Cimahi. The data collection technique was carried out by giving pre-test and post-test questions about the Pythagorean theorem. The results showed: a) The percentage of complete student learning outcomes at the beginning of the meeting was 0.0% with an average value of 21.73, b. The percentage of completeness in the first cycle is 46.6% with an average value of 58.4, c) The percentage of completeness in the second cycle is 86.6% with an average value of 77.2. Based on the results of the research, can be concluded that the Problem Based Learning (PBL) learning model can improve student learning outcomes on the Pythagorean theorem material.